India - Land Policies for Growth and Poverty Reduction - World Bank (Washington, DC, 2012)
In India, land continues to be of enormous economic, social, and symbolic relevance. The main purpose of this report is to review new empirical evidence on land administration and land policy, as well as the possible interaction between the two, to derive policy conclusions. The empirical basis for the discussion of land administration is provided by a review of land records, survey and settlement, and land registration in 14 states. Chapter two describes the origin, nature, and main functions of current institutions and the ensuing problems for secure tenure and easy transferability of land. Chapter three identifies elements of a best practice approach to improving textual data (records and registration) and, based on a review of state experience, identifies the associated benefits. Chapter four reviews the extent to which lessons from improving textual records could help to give a boost to improvement of the spatial database for land administration. Chapter five concludes the discussion on land administration by assessing the scope for title registration to help improve tenure security in India and by identifying that need to be discussed. Chapter 6 highlights that land reform has helped increase accumulation of physical and human capital but that the impact is declining over time. Chapter 7 explores the functioning of land lease markets, and the extent to which restrictions on land leasing reduce the scope for productivity and equity enhancing transfers through such markets which could be particularly beneficial for women. Chapter 8 reviews the operation of land sales markets and suggests alternative approaches for preventing land loss by tribal people and chapter 9 concludes with a series of policy recommendations.